Analisis Mikrobiologi Stik Kentang Goreng di Cafe Lesehan Talise Palu - Rizki Purnamasari; Umrah Umrah; Muhammad Alwi (Biocelebes, 2013)
Research entitling "Microbiological Analysis of Stik Potato Fry in Cafe Lesehan Talise Palu" have been executed in March until May 2013 as a mean to analyse the cemaran microbe of at stik potato fry in Cafe Lesehan Talise Palu and to know what stik potato fry the have fulfilled the Health Standard specified by BPOM by mikrobiologis. Result of research indicate that pursuant to microbiological analysis quantitatively is ALT And MPN of at sampel stik potato fry in Cafe Lesehan Talise Palu show 2 sampel which is not growed by colony, 6 sampel which is < 3,0 x 104 CFU/g, 1 incalculable sampel and 1 sampel with the result 3,1 x 104 CFU/g for the ALT of bacterium, while for the ALT of kapang obtained by 1 sampel which is not growed by the colony and 9 sampel which is < 3,0 x 104 CFU/g, and also for the ALT of khamir obtained by 3 sampel which is not growed by the colony, 6 sampel which is < 3,0 x 104 CFU/g and 1 sampel with the result 3,7 x 104 CFU/g. Most Probable Number (MPN) show 9 sampel which is 3,0 x 100 MPN/g (<3) and 1 sampel with the result 2,3 x 101 MPN/g namely Cafe C. From examination result 10 sampel stik potato fry knowable that 90% still fulfill the Health Standard specified by Director General BPOM of while 10% do not fulfill the Health Standard specified by Director General BPOM. Keywords: Microbiological Analysis, Stik Potato Fry, ALT and MPN